Instilling Character Values in Ecosystem Material and Harmonization in Elementary School Students' Science Learning - Mirasantika, Mirasantika; Nurnaningsih, Nurnaningsih; Edy Suparjan (Yayasan Insan Mulia Bima, 2025)
The purpose of this study is to describe the instillation of character values ​​in ecosystem and harmonization materials in social studies learning. The research method used is a literature study, by reviewing various sources that discuss the topic being studied. Data is collected systematically and analyzed to obtain generalizations of the topics raised. In addition to tracing written sources, researchers also adjust the data to current conditions. The results of the study indicate that the application of outdoor/outdoor learning methods can be used to instill character values ​​in ecosystem and harmonization materials, in this case students can directly witness phenomena related to learning topics, and can internalize the values ​​of wisdom in the surrounding environment as a reflection of character values. In addition, teachers also use BBL, PBL, PjBL, CTL methods, the use of videos and increasing systematic thinking skills significantly increase the instillation of character values ​​such as responsibility, cooperation, and environmental awareness, as well as improve student learning outcomes. This study contributes to the development of effective innovative learning strategies to integrate character education in IPAS learning